(untitled) (Faridpur Medical College Journal, 2021)
Glanzmann’s Thrombasthenia (GT) is a rare inherited autosomal recessive platelet functional disorder. Due to the deficiency of platelet function, it manifests as a bleeding disorder characterized by mucocutaneous hemorrhage of varying severity. It is difficult to diagnose as it closely mimics with others bleeding disorder, so it can be diagnosed after investigations & exclusion of others. Treatment is supportive care with platelet transfusion & proper counseling. With careful supportive care, GT has a very good prognosis. In this report, we describe a 13 years old female with Glanzmann Thrombasthenia. Faridpur Med. Coll. J. 2020;15(2): 103-105